STRATEGI REPOSITIONING DALAM MENGHADAPI PERUBAHAN LINGKUNGAN BISNIS DAN UPAYA MENINGKATKAN DAYA SAING PERUSAHAAN - , Dian Paramita ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This thesis aims to provide a firm recommendation strategy formulation that is engaged in the management and development of the industrial area after a change in the business environment free from monopoly to competition resulted in a paradigm shift in the PT X. A change in the business environment both internally and externally and the paradigm shift in PT X be addressed by repositioning corporate strategy formulation. The effects of changing paradigms and strategies have an impact on corporate culture. This study uses SWOT analysis model and Force Five, reinforced by the results of customer satisfaction surveys, survey and positioning services firm expectations. SWOT analysis of the results showed that the main resource PT X contained in the land and location advantage to corporate power. However, the remaining land is only 2 % of the total area of 500 ha in Pulogadung industry. With all its limitations PT X seeks to maximize the use of land and being oriented towards customer satisfaction by improving company services. Orientation changes must be supported with the right strategy at the same time transforming the corporate cultures. PT X so far have not extending the land at a different location, so that the product diversification strategy of choice. Limitations of the remaining land is circumvented by developing other products such as warehousing services , telecommunications network services through X Net and supply chain management through the X logistics . The addition of other products is expected to meet customer needs while enhancing the company's services. Recommended generic strategy for new products that no one has a different market to the other. A change in the business environment PT X requires both internal and external corporate culture transformation. The role of corporate leaders is crucial in determining the success of the corporation. Support, commitment, values and leadership styles affect the success of cultural change. Corporate success in achieving a goal is not only determined by the technical implementation through appropriate strategies but also non-technical factors that must be addressed with a wise and prudent.